Awareness of postmenopausal women about the risk of osteoporosis (literature review) - Vyrva, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Osteoporosis is a systemic disease of the skeleton, characterized by a decrease in bone mass and qualitative changes in bone structure, which lead to increased fragility and increased risk of fractures. Objective. To analyze the published information on the awareness of women in the United States, Europe and Ukraine about the risk of osteoporosis in the postmenopausal period. It is estimated that in general, about 50 % of postmenopausal women in most countries do not receive osteoporosis drug therapy and are unaware of the different treatment options for disease, 25 % associate it only with femur and spine fractures. Surveys have found that most respondents without a diagnosis of osteoporosis have had one or more risk factors for developing it, but osteoporosis is often not diagnosed until one or more fractures have occurred. That is why orthopedists-traumatologists, who most often face pathological fractures on the background of osteoporosis, have proposed special protocols for the timely diagnosis and treatment of fragile  fractures. Treatment standards require women aged 65–85 who have suffered a fracture to be screened and receive osteotropic therapy for 6 months. However, the diagnosis and treatment of osteoporosis for 6 and 12 months after femoral neck fractures received only 17–23 % of respondents. Misconceptions about the causes and consequences of postmenopausal women fractures, combined with insufficient information from health professionals, point to the low level of attention of the population and the health care system in general to osteoporosis in all countries. The incidence of fractures in women was 3.1 higher than in men and progressively increased the age 50+. For high risk fractures women due to osteoporosis ensuring their osteoporosis awareness is a critical preventive point. This is essentialy can influence positive changes in the fight against osteoporosis around the world. Osteoporosis is a systemic disease of the skeleton, characterized by a decrease in bone mass and qualitative changes in bone structure, which lead to increased fragility and increased risk of fractures. Objective. To analyze the published information on the awareness of women in the United States, Europe and Ukraine about the risk of osteoporosis in the postmenopausal period. It is estimated that in general, about 50 % of postmenopausal women in most countries do not receive osteoporosis drug therapy and are unaware of the different treatment options for disease, 25 % associate it only with femur and spine fractures. Surveys have found that most respondents without a diagnosis of osteoporosis have had one or more risk factors for developing it, but osteoporosis is often not diagnosed until one or more fractures have occurred. That is why orthopedists-traumatologists, who most often face pathological fractures on the background of osteoporosis, have proposed special protocols for the timely diagnosis and treatment of fragile  fractures. Treatment standards require women aged 65–85 who have suffered a fracture to be screened and receive osteotropic therapy for 6 months. However, the diagnosis and treatment of osteoporosis for 6 and 12 months after femoral neck fractures received only 17–23 % of respondents. Misconceptions about the causes and consequences of postmenopausal women fractures, combined with insufficient information from health professionals, point to the low level of attention of the population and the health care system in general to osteoporosis in all countries. The incidence of fractures in women was 3.1 higher than in men and progressively increased the age 50+. For high risk fractures women due to osteoporosis ensuring their osteoporosis awareness is a critical preventive point. This is essentialy can influence positive changes in the fight against osteoporosis around the world.